THE PERCEPTION AND APPLICATION OF BLENDED LEARNING AS A LEARNING ALTERNATIVE IN THE INDUSTRY 4.0 ERA - Cipto Wardoyo; Yogi Dwi Satrio; Citra Kusuma (Universitas Muria Kudus, 2022)
The purpose of this study is to look at the perceptions and application by Accounting teachers of blended learning as an alternative to learning in the 4.0 era.The research method used is qualitative with the type of case study research. Informants were determined by using a purposive sampling technique. The criteria are teachers who apply blended learning and students who receive blended learning at the Accounting Department of SMKN 2 Blitar. Primary data sources were obtained from teachers and students through in-depth interviews regarding the application of blended learning as an alternative learning in the Industry 4.0 era and secondary data obtained from teacher documentation, training activities and assistance in using technology in learning. Data collection techniques were carried out by means of interviews, observation and documentation. Data analysis was performed using data reduction, data presentation, conclusion and verification. Checking the validity of the findings was carried out using source triangulation techniques and technique/method triangulation techniques.The results of the study show that 1) accounting teachers and students give positive perceptions about the application of blended learning as an alternative for learning in the 4.0 era; 2) two accounting teachers have implemented blended learning, namely combining face-to-face learning with online e-learning such as Gnomio and Google Classroom, while five accounting teachers have not implemented blended learning due to several obstacles; 3) the perceptions of teachers and students show that the application of blended learning has an impact on student learning motivation, such as independent learning, being active in teaching and learning activities and collecting assignments on time.